1984
DOI: 10.3102/00346543054002225
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nonpromotion on Elementary and Junior High School Pupils: A Meta-Analysis

Abstract: In this study data from all studies identified as meeting the selection criteria were mathematically integrated to determine the effect of grade-level retention on elementary and/or junior high school pupils. When each effect size calculated was treated equally, a grand mean effect size of -.37 was obtained indicating that, on the average, promoted children scored .37 standard deviation units higher than retained children on the various outcome measures. When the effect sizes within each study were first avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
1
8

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(134 citation statements)
references
References 3 publications
3
122
1
8
Order By: Relevance
“…Results of studies of retention's effects on achievement have also been mixed, though predominantly negative (for reviews see Holmes & Matthews, 1984;Jimerson, 2001;Shepard & Smith, 1990.). When interpreting results of such studies, it is important to distinguish studies that used same-age comparisons from those that used same-grade comparisons.…”
Section: Grade Retention and Variables Associated With Peer Acceptancementioning
confidence: 99%
See 2 more Smart Citations
“…Results of studies of retention's effects on achievement have also been mixed, though predominantly negative (for reviews see Holmes & Matthews, 1984;Jimerson, 2001;Shepard & Smith, 1990.). When interpreting results of such studies, it is important to distinguish studies that used same-age comparisons from those that used same-grade comparisons.…”
Section: Grade Retention and Variables Associated With Peer Acceptancementioning
confidence: 99%
“…Passage in 2002 of the No Child Left Behind Act, with its emphasis on mastery of minimum grade-level competencies as a condition for promotion, has renewed discussion of grade retention in the public arena. However, many researchers have examined the effects of grade retention during childhood and adolescence (Alexander, Entwisle, & Dauber, 1994 BeebeFrankenberger, Bocian, MacMillan, & Gresham, 2004;Holmes & Matthews, 1984;Jimerson, 1999Jimerson, , 2001Jimerson, Carlson, Rotert, Egeland, & Sroufe, 1997;Mantzicopoulos, 1997;Mantzicopoulos & Morrison, 1992;McCoy & Reynolds, 1999;Meidel & Reynolds, 1999;Meisels & Liaw, 1993;Rumberger, 1995;Shepard & Smith, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two national studies found retention rates of 21.3% (Resnick et al, 1997) and 20% (Rumberger, 1995). Numerous meta-analyses, reviews, and individual research papers report negative effects of grade retention (e.g., Holmes, 1989;Holmes & Matthews, 1984;Jimerson, 2001;Shepard & Smith, 1990;Silberglitt, Appleton, Burns, & Jimerson, 2006). The most recent of these meta-analyses found negative effects in terms of students' academic, socioemotional, and behavioral outcomes when retained students were compared to similar students promoted to the next grade (Jimerson, 2001).…”
Section: Grade Retentionmentioning
confidence: 99%
“…Retention continues to be a common form of intervention for students who have been deemed unprepared for the next level of cognitive and social development, despite the known deleterious impacts on student dropout rate, attitudes towards school, and engagement (Schnurr, Kundert, & Nickerson, 2009). Schnurr et al (2009) cite multiple examples of research on retention and academic outcomes, with findings indicating small short-lived improvements in achievement (Jimerson, 2001;Gleason, Kwok, & Hughes, 2007) but no long-term improvement for retained students (Holmes & Matthews, 1984;Holmes, 1989;Jimerson, 2001). Further, the long-term impacts of retention on student performance have been shown to be nonsignificant (Jimerson, 1999;Silberglitt, Jimerson, Burns, & Appleton, 2006;Jimerson & Ferguson, 2007).…”
Section: Grade Repetition (Retention)mentioning
confidence: 99%